The Cognitive Ageing, Nutrition and Neurogenesis (CANN) trial: Design and progress. Issue 1 (4th September 2018) - Irvine, Michael A.; Scholey, Andrew; King, Rebecca; Gillings, Rachel; Vauzour, David; Demichele, Stephen J.; Das, Tapas; Wesnes, Keith A.; Sutton, Brad P.; Cassidy, Aedin; Pipingas, Andrew; Potter, John F.; et al.
Abstract: Introduction: The Cognitive Ageing, Nutrition and Neurogenesis trial hypothesizes that a combined intervention with long‐chain n‐3 polyunsaturated fatty acids (n‐3) and cocoa flavan‐3‐ols (FLAV) will mitigate the cognitive decline anticipated to naturally occur over 1 year in older adults. Methods: In a double‐blinded, placebo‐controlled parallel design, 259 individuals with mild cognitive impairment or subjective memory impairment were randomized to a control or n‐3 FLAV group (1.5 g docosahexaenoic acid + eicosapentaenoic acid and 500 mg n‐3 FLAV daily) for 12 months. Cognition was measured at 0, 3, and 12 months. The primary end‐point is hippocampus‐sensitive cognitive function (e.g., number of false‐positives on the Picture Recognition Task of the Cognitive Drug Research test battery). Secondary outcomes include additional cognitive measures, brain atrophy and blood flow (assessed by magnetic resonance imaging), vascular function, circulating biomarkers of cardiovascular and cognitive health, gut microflora, red blood cell fatty acid status, and urine flavan‐3‐ol metabolites. Results: Screening began in 2015, with all baseline visits completed in March 2017. The intervention was finished in March 2018. Discussion: Cognitive Ageing, Nutrition and Neurogenesis aims to identify an effective diet‐based intervention to prevent or delay cognitive impairment in cognitively at‐risk individuals, which could ultimately contribute to a reduced population burden of dementia. Clinicaltrials.gov: NCT02525198 .